The uneasy case for progressive taxation - Blum, Walter J.; Kalven, Harry (Chicago : University of Chicago Press, 1953)
A decade has passed since the publication of this essay. We are pleased to have the excuse of its republication to return to the perplexities of the case for progressive taxation.
Authors' names in reverse order in 1952 edition.
Published in 1976 under title: The uneasy case of progressive taxation in 1976, by W. J. Blum.
Includes index.
uaa 24/01/2019
Loans
Keywords: Progressive taxation; Income tax; United States